Operational Process for Manufacturing a MEMS Micro-Cantilever System - Kafumbe, Said; Ravichandran, Danthakani; Emad, Abd-Elrady; Mohammad, Alqudah; Alun, Harris; Jim, Burdess (IEEE, 2015)
The processing techniques and materials utilized in the fabrication of a two-terminal electrostatically actuated micro electro-mechanical (MEMS) cantilever-arrayed device used for radio frequency tuning applications are presented in this work. The process is based on silicon surface micromachining with spin-coated photoresist as the sacrificial layer placed underneath the electroplated gold structural material and an insulating layer of silicon dioxide. Silicon dioxide layer is deposited using plasma enhanced chemical vapour deposition (PECVD), to avoid a short circuit between the cantilever and the bottom electrode. The fabrication process involves six major steps designed under controlled experiments. These includes the plasma enhanced chemical vapour deposition of the silicon dioxide insulating layer, optical lithography to transfer photomask layer patterns, vacuum evaporation to deposit thin films of Titanium (Ti) and Gold (Au), electroplating of Au, the dry release of the cantilever beam arrays, and finally the wafer dicing to split the different micro devices. These process steps were each sub-detailed to give a total of fourteen micro-fabrication processes. Scanning electron microscope (SEM) images taken on the final fabricated device that was dry released using oxygen plasma ashing to avoid stiction, showed twelve freely suspended micro-cantilevered beams suspended with an average electrostatic gap of 2.29±0.17 microns above a 4934±3 angstrom thick silicon dioxide layer. Preliminary dimensional measurements on the fabricated devices revealed that the cantilevers were at least 52.06±1.93 microns wide with lengths varying from 377.97±0.01microns to 1491.89±0.01 microns, and were at least 2.21±0.05 microns thick. These results were validated by design values
Keywords: MEMS; Micro-Cantilever; Manufacturing process; Gold electrodeposition